The influence that JavaScript(TM) has on the visibility of a Website to search engines - a pilot study - M. Weideman; F. Schwenke (Information Research: An International Electronic Journal)
Introduction. In this research project, an empirical pilot study on the relationship between JavaScript(TM) usage and Website visibility was carried out. The main purpose was to establish whethe JavaScript(TM)-based hyperlinks attract or repel crawlers, resulting in an increase or decrease in Website visibility. Method. A literature survey has established that there appears to be contradiction amongst claims by various authors as to whether or not crawlers can parse or interpret JavaScript(TM). The chosen methodology involved the creation of a Website that contains different kinds of links to other pages, where actual data files were stored. Search engine crawler visits to the page pointed to by the different kinds of links were monitored and recorded. Analysis. This experiment took into account the fact that JavaScript(TM) can be embedded within the HTML of a Web page or referenced as an external '.js' file. It also considered different ways of specifying links within JavaScript(TM). Results. The results obtained indicated that text links provide the highest level of opportunity for crawlers to discover and index non-homepages. In general, crawlers did not follow Javascript(TM)-based links to Web pages blindly. Conclusion. . Most crawlers evade Javascript(TM) links, implying that Web pages using forms of this technology, for example in pop-up/pull-down menus, could be jeopardising their chances of achieving high search engine rankings. Certain Javascript(TM) links were not followed at all, which has serious implications for designers of e-Commerce Websites.